The Effect Of Preventive Maintenance And Breakdown Maintenance On The Smooth Running Of The Production Process (Case studies on CV. Dira Mahakarya Utama of Ciamis Regency Printing) - Agus Nurhidayat; Suci Putri Lestari; Rita Tri Yusnita (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the Effect of Preventive Maintenence and Breakown Maintenence on the smooth running of the Production Process (Case study on CV. Dira Mahakarya Utama Printing Ciamis Regency). The method used in this study is a casual associative method (causation) with a quantitative approach, as for what is used as a sample, namely data on preventive maintenence costs, maintenence breakdown costs, and production target data for the last 4 years, namely in the 2018-2021 period at the Dira Mahakarya Utama printing house. The analysis tool used in this study was multiple linear regression using SPSS Version 25. The results showed that simultaneously the disciplines of Preventive Maintenence and Breakdown Maintenence had a significant effect on the smooth running of the production process. Partially Preventive Maintenence has a significant effect on the smooth running of the production process. Partial Breakdown Maintenence does not have a significant effect on the smooth running of the Production Process.